Crime Prevention Through Community Policing Interventions: Evidence from Harar City, Eastern Ethiopia - Melese Teferi Adugna; Tesfaye Zeleke Italemahu (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
In Ethiopia, community policing has been announced ofcially as a national program in 2005 E.C with the impetus to nullify crimes at lower tiers. There have been growing reports of prevailing crimes in Jenila district of Harar city. Accordingly, this study endeavors to scrutinize the practices of community policing and associated challenges in the study site. A mixed research deign was used to fetch out primary and secondary data sets. Hence, the participants’ views were captured through questionnaires, key informant interviews and focused group discussions. The data were analyzed using descriptive statistics such as frequency, bar graph and percentages. The fnding of the study revealed that a greater proportions of the respondents recognized that community policing practices had contributed in preventing crimes; burglary 94 (27%) and robbery 77 (22%) as most frequently recurring and reported types of crimes in the city. While community policing structures and concerned actors operate to smoothly run the programs, there were cropping up predicaments at the grass root levels. Limited awareness among the residents, inadequate fnancial resources and professionally ill-qualifed human power were reported as major obstructions. In the face of increasing crimes, both in terms of intensity and types on the one hand, and intricate challenges to penetrate through on the other hand, the communities of residents aspire to dive deep with a sense of ownership and exploit the opportunities for intensifying the programs stated in community policing programs. Eventually, there was need to move in concerted manner to lessen the impacts of crimes in Jenila district of Harar city.